Product innovation and renewal: foreign firms and clusters in Belgium - Filip De Beule; Ilke Van Beveren (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
Using the cluster definitions of the European Cluster Observatory, this paper investigates the link between cluster membership and firm-level product innovation and renewal,using data from the Community Innovation Survey for Belgium. Clustered firms account for 71 percent of total product renewal generated in 2004 and for 53 percent of product innovators; compared to 29 and 47 percent for non-clustered firms, respectivily. Furthfirmore, cluster membership is shown to be conducive to firm-level product innovation and renewal once firm size, export intensity and reseach inputs are taken into account. Foreign firms are not more prone to carry out product innovation, except for subsidiaries in clusters.
Keywords: D21; F23; O31; O33; 330; Product Innovation; Clusters; Community Innovation Survey; Multinational Firms